Neuroprotective and antimalarial effects of Juglans regia leaf extracts in a murine model of cerebral malaria - Alharbi, Afra; Albasyouni, Shurug; Al-Shaebi, Esam; Al Quraishy, Saleh; Abdel-Gaber, Rewaida (Frontiers in Veterinary Science, 2025)
BackgroundMalaria is a major public health problem caused by the apicomplexan Plasmodium parasite. Cerebral malaria (CM) is the most critical outcome of Plasmodium infection. It is becoming more difficult to manage, particularly in areas of multi-drug resistance. Scientists are focused on identifying alternative strategies to combat malaria infection. Therefore, this study was designed to evaluate the activity of Juglans regia leaf extract (JRLE) in Plasmodium berghei-infected C57BL/6 mice.MethodsThe J. regia leaf extract (JRLE) was prepared using methanol and characterized by Fourier-transform infrared spectroscopy (FT-IR). Female C57BL/6 mice were divided into six groups (5 mice/group): control, non-infected but JRLE-treated (500 mg/kg), P. berghei-infected non-treated, and P. berghei-infected treated with JRLE (250 or 500 mg/kg) or chloroquine (10 mg/kg). Groups (3–6) were infected intraperitoneally with P. berghei (1 × 10⁵). Treatment (oral JRLE or chloroquine) was administered for 5 days starting on day 4. Parasitemia, survival, and body weight were assessed, and brains were collected on day 9 p.i. for histopathological analysis (H&E staining) and GFAP immunohistochemistry. GABA, glutamate, neurotransmitters (epinephrine, norepinephrine, dopamine, serotonin), and mRNA expression of signaling genes (Chrnb2, Gabbr1, Gnai1, Gria2) were evaluated using ELISA and real-time PCR.ResultsPhytochemical screening by FT-IR demonstrated the presence of 10 functional groups in the JRLE. By day 9 after infection with the P. berghei parasite, the parasitemia was significantly reduced after JRLE treatment with a dose of 500 mg/kg (6.33% ± 1.18%) compared to the infected group (23.84% ± 2.06%) with a positive correlation with body weight. Our data showed that JRLE prolonged the survival curve of the infected mice. JRLE ameliorates the reduction of the brain index caused by P. berghei infection. Furthermore, histological analysis showed that infection with P. berghei exacerbates brain damage as evidenced by degeneration of Purkinje cells, cerebral hemorrhage, intravascular sequestrations of parasitized red blood corpuscles (pRBCs), and infiltration of lymphocytes. At the same time, treatment with JRLE mitigates the brain injury induced by the infection. JRLE reduced the level of GFAP expression in the brain tissue of the infected mice. Additionally, treatment with JRLE ameliorates the brain neurotransmitter disbalance (i.e., epinephrine, norepinephrine, dopamine, and serotonin) after Plasmodium infection. Upon JRLE treatment, Chrnb2, Gnai1, and Gabbr1 mRNA expression were down-regulated in the brain tissues derived from infected female C57BL/6 mice. Meanwhile, mRNA expression of Gria2 was up-regulated after JRLE inoculation. Our study proved that JRLE significantly ameliorated the neurotransmitter markers by increasing GABA levels and decreasing the glutamate level in the brain of P. berghei-infected mice.ConclusionTaken together, the data reported here illustrate that J. regia leaf extracts possess potent antimalarial effects and may offer a potential drug lead for developing a safe, effective, and affordable antimalarial therapy. Further studies are recommended to include the broader organ-specific effects of plant extract.